No one will miss her ebook A novel. - Rosenfield, Kat (2021)
"Blade-sharp, whip-smart, and genuinely original — a thriller to refresh your faith in the genre, your belief that a story can still outpace and outsmart you."— A. J. Finn, #1 New York Times bestselling author of The Woman in The Window "Clever and surprising...The superb character-driven plot delivers an astonishing, believable jolt."—Publishers Weekly (starred review) "Deserves two big thumbs up. Readers will be gripped by this astonishing story in which one gasp-inducing twist follows on the heels of another. A unique page-turner that just begs to be turned into a movie." —Booklist (starred review) "Sly, sinister...a white-knuckled read. There are gasp-worthy surprises, of course, and the exquisite and lurid twists will reveal themselves in time."—Vanity Fai r A smart, witty, crackling novel of psychological suspense in which a girl from a hardscrabble small town meets a gorgeous Instagram influencer from the big city, with a murderous twist that will shock even the most savvy reader. On a beautiful October morning in rural Maine, a homicide investigator from the state police pulls into the hard-luck town of Copper Falls. The local junkyard is burning, and the town pariah Lizzie Oullette is dead—with her husband, Dwayne, nowhere to be found. As scandal ripples through the community, Detective Ian Bird's inquiries unexpectedly lead him away from small-town Maine to a swank city townhouse several hours south. Adrienne Richards, blonde and fabulous social media influencer and wife of a disgraced billionaire, had been renting Lizzie's tiny lake house as a country getaway...even though Copper Falls is anything but a resort town. As Adrienne's connection to the case becomes clear, so too does her connection to Lizzie, who narrates their story from beyond the grave. Each woman is desperately lonely in her own way, and they navigate a relationship that cuts across class boundaries: transactional, complicated, and, finally, deadly. A Gone Girl for the gig economy, this is a story of privilege, identity, and cunning, as two devious women from opposite worlds discover the dangers of coveting someone else's life. "Both amusingly satirical and darkly bloody."—The Washington Post